Trend and Current Status of Child Injury Fatalities in Thailand Compared with Sweden and Japan - Adisak Plitponkarnpim (2018)
The aim of this paper was to analyze the trend and current pattern of child injury fatalities in Thailand and compare them to those in Sweden and Japan. The experiences in these higher-income countries will help identify potential crucial areas that might be beneficial to Thailand. In 1996, a total of 4153 Thai children died of injuries, of which two-thirds were due to drowning or transport crashes. Drowning was the leading cause of death in all age-gender groups except for boys aged 10-14 years. Compared to those in Sweden and Japan, a substantial difference in mortality rates was observed, especially drowning deaths in girls aged 5-14 years. Contrary to Sweden and Japan, injury death rates in Thai children showed increasing trends between 1987 and 1996. To improve child survival, recognizing injury as a major child health problem, expanding safety research, and implementing safety promotion programs are crucial factors. © 1999 National Safety Council and Elsevier Science Ltd.